Systemic Sclerosis, Reversible Cerebral Vasoconstriction Syndrome, and NeuroMyelitis Optica in a Patient - Masoud Etemadifar; Mehdi Shafiei; Mehri Salari; Ali Modares Sadeghi; Mohammad Fakhrolmobasheri (Case Reports in Immunology)
Systemic sclerosis (SSC) is an autoimmune disease of connective tissue and microvasculature mostly caused by autoantibodies. Likewise, neuromyelitis optica (NMO) is a demyelinating disease of the central nervous system correlating with autoantibodies against aquapourin-4. Reversible cerebral vasoconstriction syndrome (RCVS) is a disorder of brain vasculature resembling Raynaud phenomena in SSC. Despite co-occurrence is not rare in autoimmune disorders, the co-occurrence of NMO and SSC is extremely rare. In this case, we report a 35-year-old female presenting with paraplegia one day after discharge from hospital following surgical carnioplasty. She had a history of scleroderma and optic neuritis for which she was treated with high dose glucocorticoids causing renal crisis and RCVS causing intracranial and intracerebral hemorrhage which required a craniotomy to be performed in February 2020. In her recent admission, magnetic resonance imaging of the spinal cord indicated longitudinally extensive transverse myelitis (LETM) and blood tests revealed a highly positive titer of NMO-IgG. Daily plasmapheresis resulted in satisfactory improvement in her condition. This case highlights the importance of evaluating neurologic manifestations in systemic sclerosis patients considering the NMO and RCVS occurrence. Additionally, in concomitant cases, the treatment strategy should be modified regarding the risk of scleroderma renal crisis.